2013
DOI: 10.5433/1679-0359.2013v34n6supl2p4053
|View full text |Cite
|
Sign up to set email alerts
|

Interferência da dieta de alto grão sobre as características da carcaça e carne de cordeiros Texel

Abstract: ResumoEste estudo teve como objetivo estudar o efeito de dietas com diferentes proporções de concentrado na terminação de cordeiros Texel sobre as características das carcaças e carne ovina. Foram utilizados 12 cordeiros da raça Texel com peso inicial de 20,1±2,34kg. Foram avaliadas rações com três proporções de concentrado na ração total (60, 80 e 100%) e quatro repetições por tratamento. O concentrado foi composto por 15%suplemento nutricional + 85% grão de milho inteiro e o volumoso foi feno de Aveia (Avena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
3
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
5
3
1
2
Order By: Relevance
“…Values of HCY and CCY were not affected (P ≥0.05) by the addition of BLH or BPH in the diet, as the yields were calculated by the ratio between the weight of cold or hot carcasses and the weight when slaughtered. Mean values of 47.1 and 45.7 for HCY and CCY are in agreement with those reported in the literature for Santa Inês lambs (LIMA et al, 2013;SILVA et al, 2014;RODRIGUES et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…Values of HCY and CCY were not affected (P ≥0.05) by the addition of BLH or BPH in the diet, as the yields were calculated by the ratio between the weight of cold or hot carcasses and the weight when slaughtered. Mean values of 47.1 and 45.7 for HCY and CCY are in agreement with those reported in the literature for Santa Inês lambs (LIMA et al, 2013;SILVA et al, 2014;RODRIGUES et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…According to Fernandes et al (2011), when animals of the same breed have equivalent body conformation, their carcass weight, carcass yield, and relative weight of meat cuts are also similar. Lima et al (2013) assessed Texel lambs with SBW of 40.6 kg and found shoulder, neck, rib, and leg yields of 19.3, 5.72, 41.4, and 32.6 kg/100 kg of CCW, respectively, values that closely match those reported here. Cutting the carcass into specific parts that suit different consumers optimizes yield, avoids waste, and allows for adequate pricing (Silva Sobrinho and Silva, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…The average HCY (49.4 kg/100 kg SBW) found for non-castrated male lambs (¾ Texel + ¼ Pantaneiro) in our study was higher than that reported by Carvalho and Medeiros (2010) for non-castrated male lambs (½ Texel + ½ undefined; 47.4 kg/100 kg SBW). Lima et al (2013) also published HCY (48.7 kg/100 kg SBW) and CCY (47.2 kg/100 kg SBW) for male Texel lambs that were lower than those found in the present work. Thus, we found good HCY (49.4 kg/100 kg SBW) and CCY (48.1 kg/100 kg SBW) that fell within the ideal range of 40 to 50 kg/100 kg SBW established for meat-producing sheep breeds, such as Texel (Silva Sobrinho, 2006).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…De acordo com Lima et al (2013), os valores de perdas por resfriamento observados neste estudo (3,41%, em média) estão dentro dos níveis máximos considerados aceitáveis para cordeiros, que variam de 3 a 4%, demonstrando que o critério de abate estabelecido de escore de condição corporal igual a 3 conferiu adequado grau de acabamento e quantidade de gordura de cobertura (valor médio foi de 2,56mm) satisfatória na carcaça dos animais.…”
Section: Resultsunclassified